A20 regulates the therapeutic effect of anti-PD-1 immunotherapy in melanoma. Issue 2 (9th December 2020) - Guo, Weinan; Ma, Jinyuan; Guo, Sen; Wang, Huina; Wang, Sijia; Shi, Qiong; Liu, Lin; Zhao, Tao; Yang, Fengfan; Chen, Shuyang; Chen, Jianru; Zhao, Jianhong; et al.
Abstract : Background: The therapeutic effect of immune checkpoint blockers, especially the neutralizing antibodies of programmed cell death (PD-1) and its ligand programmed death ligand 1 (PD-L1), has been well verified in melanoma. Nevertheless, the dissatisfactory response rate and the occurrence of resistance significantly hinder the treatment effect. Inflammation-related molecules like A20 are greatly implicated in cancer immune response, but the role of tumorous A20 in antitumor immunity and immunotherapy efficacy remains elusive. Methods: The association between tumorous A20 expression and the effect of anti-PD-1 immunotherapy was determined by immunoblotting, immunofluorescence staining and flow cytometry analysis of primary tumor specimens from melanoma patients. Preclinical mouse model, in vitro coculture system, immunohistochemical staining and flow cytometry analysis were employed to investigate the role of A20 in regulating the effect of anti-PD-1 immunotherapy. Bioinformatics, mass spectrum analysis and a set of biochemical analyzes were used to figure out the underlying mechanism. Results: We first discovered that upregulated A20 was associated with impaired antitumor capacity of CD8 + T cells and poor response to anti-PD-1 immunotherapy in melanoma patients. Subsequent functional studies in preclinical mouse model and in vitro coculture system proved that targeting tumorous A20 prominently improved the effect of immunotherapy through the invigoration of infiltrating CD8 + T cells via the regulation of PD-L1. Mechanistically, A20 facilitated the ubiquitination and degradation of prohibitin to potentiate STAT3 activation and PD-L1 expression. Moreover, tumorous A20 expression was highly associated with the ratio of Ki-67 percentage in circulating PD-1 + CD8 + T cells to tumor burden. Conclusions: Together, our findings uncover a novel crosstalk between inflammatory molecules and antitumor immunity in melanoma, and highlight that A20 can be exploited as a promising target to bring clinical benefit to melanomas refractory to immune checkpoint blockade.